ASURANSI KESEHATAN KUMPULAN UNTUK PERAWATAN RUMAH SAKIT - munadi, MUnadi; sunarsih, Sunarsih (MATEMATIKA, 2009)
Health insurance is a guarantee to minimize financial loss from sickness. Group health insurance spital care is health insurance. Health insurance used for Pegawai Negeri Sipil (PNS) and retering PNS and TNI/Polri and also their family that called ASKES service insurance. Computation hospital health insurance premiums affected by age and sex, also use Daily Hospital Benefit table for group health insurance, while ASKES service premiums based on class and work time and the computation and fixed by Departemen Keuangan Republik Indonesia. To difference between group health insurance premiums with ASKES service premiums for hospital care is grat 1:7. Â